Treinamento funcional como conteúdo nas aulas de Educação Física no ensino médio: uma revisão bibliográfica - Silva, Edna Cristina da (Brasil, 2023)
This bibliographic study aimed to bring information about the Functional Training (TF) method as content in Physical Education classes in High School. The search was carried out in books and articles in the databases, which contemplated the relationship between functional training and physical fitness aimed at improving student’s daily activities. The ST aims to improve functional capabilities through basic human movements, such as pushing, squatting, jumping, throwing, walking, running, with or without the use of material; in a dynamic, playful and relaxed way where everyone can participate and understand the importance of physical activity in their daily lives, as well as its benefits throughout life. The TF as content in physical education can be used as methodological instrument for the development of the element corresponding to the field of personal and collective life of the student, according to the field of social action foreseen by the BNCC for the new high school.